Efficacy of three-dimensional endoscopy in endonasal surgery. Issue 3 (June 2015) - Ogino-Nishimura, Eriko; Nakagawa, Takayuki; Sakamoto, Tatsunori; Ito, Juichi
Abstract Objective To examine the efficacy of a three-dimensional (3D) endoscope for endoscopic sinus and skull base surgery. Methods The study design was a retrospective case series and qualitative research. The clinical efficacy of 3D endoscopes was examined on five cadavers. We performed conventional endoscopic sinus surgery (ESS) in five cases and hypophysectomy in two cases using a 3D endoscope. The educational advantages of the 3D endoscope were assessed using questionnaires given to the participants of cadaver dissection courses. Results In the posterior portion of the nasal cavity, images captured via 3D endoscopy provided a superior perception of depth of information than those via two-dimensional (2D) endoscopy. All endonasal surgeries were completed in clinical settings using a 3D endoscope without perioperative complications. In terms of the operative time and amount of bleeding, the results of 3D endoscopic surgeries were not inferior to those of 2D endoscopic surgeries. Fatigue from 3D viewing through polarized glasses did not adversely affect performance of the surgery. Moreover, questionnaires for the evaluation of educational efficacy were completed by 73 surgeons. Of the respondents, 89% agreed that 3D endoscopy provided a better understanding of the surgical anatomy than did 2D endoscopy. As for the site where 3D endoscopy would be the most useful for understanding surgical anatomy, 40% of the respondents named the skull base; 29%, the posterior ethmoid sinuses; and 26%, the sphenoid sinus; and 9%, the ethmoid bulla and middle turbinate. Conclusion The 3D endoscope contributes to a more precise anatomical understanding of the posterior structures of the sinuses and skull base and ensures a more precise operation of the instruments. Thus, 3D endoscopes will likely become a standard device for endonasal surgery in the near future.